Structural and magnetic properties of spin-1/2 dimer compound Cu2(IPA)2(DMF)(H2O) with a large spin gap. (18th May 2017) - Thamban, S; Arjun, U; Padmanabhan, M; Nath, R
Abstract: We present the synthesis and a detailed investigation of structural and magnetic properties of metal-organic compound Cu2 (IPA)2 (DMF)(H2 O) by means of x-ray diffraction, magnetization, and heat capacity measurements. Single crystals of the title compound were synthesized by judicious selection of organic ligand and employing a selective hydrothermal reaction route. It crystallizes in an orthorhombic structure with space group Cmca . The structural analysis revealed that two Cu 2+ ions are held together by the organic component (-O-C-O-) in a square paddle-wheel to form spin dimers which are aligned perpendicular to each other and are further coupled through organic ligands (isophthalic acid) forming two-dimensional layers. Temperature dependent magnetic susceptibility χ ( T ) could be described well using spin-1/2 dimer model. The spin susceptibility χ s p i n ( T ) shows an exponential decrease in the low temperature region, below the broad maximum, confirming the singlet ground state with a large spin gap of Δ / k B ≃ 414 K. The heat capacity C p measured as a function of temperature also confirms the absence of magnetic long-range-order down to 2 K.